The Religious Question and the Change Era in Nigeria: Going Beyond Illusions - Otonko, Jake (KWASU Journal of Religious Studies, 2017)
Umpteen scholarships have identified religion as one of the many factors responsible for instability in many countries of the world especially Nigeria. This assessment is a snapshot from the central role that religion plays in the lives of typical Nigerians, indeed Africans. In this era of change, it is pertinent to evaluate how religion could make the desired change a dream come true. This paper contends that a bold step towards achieving this desired change is curbing the challenge to development posed by religion in Nigeria. Religious values have a lot to offer towards establishing a balanced and stable society. All the major religions in Nigeria share these values even though crises among these religions have not allowed these values to bloom desirably. Findings show that once religious sanity is guaranteed and the rich values in the religions in Nigeria are allowed to play out in daily affairs, the desired change will go beyond mere illusions. The analytic as well as prescriptive approach is adopted by this paper.